THE IMPACT OF DIGITAL LITERACY ON STUDENTS’ ACADEMIC PERFORMANCE AND LEARNING SKILLS - Sarvinoz Nabijonova (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: Digital literacy has become a crucial skill in the contemporary educational environment, influencing both academic performance and learning efficiency. This study investigates how students’ proficiency in digital tools, online research, and information evaluation affects their learning outcomes. A systematic review of recent literature, combined with surveys and observational studies among high school and university students, was conducted to analyze the correlation between digital literacy and academic achievement. Findings indicate that students with higher digital literacy levels demonstrate improved problem-solving skills, better information management, and increased engagement in learning activities. Additionally, digital literacy fosters independent learning, critical thinking, and adaptability in diverse academic tasks. The study also highlights challenges such as digital inequality, lack of adequate training, and over-reliance on technology, which may hinder learning efficiency. Understanding these dynamics is essential for educators, policymakers, and students themselves to implement strategies that enhance digital competencies. Consequently, promoting digital literacy not only supports academic success but also prepares students for lifelong learning in a technologically evolving society.